СТРАТЕГІЇ ТА МЕТОДИ УПРАВЛІННЯ ГЕНДЕРНИМИ КОНФЛІКТАМИ - Батрин, Наталія Володимирівна (Київ: Нік-Центр, 2010)
The article deals with important problems in Ukrainian education, in which the gender sensitive issues are not being considered as significant. The purpose of the article is to attract attention of scientists and scholars to the importance of gender policy development in the country. The article presents some statistic data and describes the basic approaches and principles in modern Ukrainian gender education.
The article deals with important problems in Ukrainian education, in which the gender sensitive issues are not being considered as significant. The purpose of the article is to attract attention of scientists and scholars to the importance of gender policy development in the country. The article presents some statistic data and describes the basic approaches and principles in modern Ukrainian gender education.
Keywords: Гендер, гендернф конфлікти, гендерна диференціація